Dactylogyrids (Monogenea) parasitic on marine fish from Peru including the description of a new species of Haliotrema Johnston & Tiegs, 1922 and two new species of Parancylodiscoides Caballero & C. & Bravo-Hollis, 1961 - Cruces, Celso L.; Chero, Jhon D.; Sáez, Gloria; Luque, José L. (Zootaxa, 2017)
A parasitological survey searching dactylogyrids (Monogenea) infesting the gills of Peruvian marine fish was carried out during the 2015–2016 period. The gills of three teleosts species, 12 Hemanthias peruanus (Steindachner), 16 Hemanthias signifer (Garman) (Serranidae) and 4 Scarus perrico Jordan & Gilbert (Scaridae), were sampled. A new species of Haliotrema and two new species of Parancylodiscoides were described: Haliotrema sanchezae n. sp. from S. perrico, Parancylodiscoides peruensis n. sp. from H. peruanus and P. signiferi n. sp. from H. signifer. Haliotrema sanchezae n. sp. differs from other congeneric species by its male copulatory organ (tapered-shaped cirrus tube, with cylinder-shaped base and a membranous, blanket-shaped accessory piece), and the morphology of its transverse bars (X-shaped ventral bar and mask-shaped dorsal bar). Parancylodiscoides peruensis n. sp. differs from all other members of Parancylodiscoides by having a tapered-shaped copulatory organ with curved distal tip and a bell-shaped base having two lateral knobs and short arm. Parancylodiscoides signiferi n. sp. can be differentiated from its congeners by its male copulatory organ, which has tubular-shaped with a loop at distal end and a slightly expanded base having a short and broad arm. Present findings are added to the other 3 marine dactylogyrid previously reported from Peru.